Implementation of Technology for High-Performance Milling of Aluminum Alloys Using Innovative Tools and Tooling - Robert Ostrowski; Marcin Szpunar; Piotr Myśliwiec; Marek Zwolak; Marek Bujny (Advances in Mechanical and Materials Engineering)
The research described in the concerns the development and implementation of new clamping technologies used in machining, particularly for thin-walled structural components of aircraft and helicopters. Among other things, the performance of the Schunk Vero-S Aviation clamping system in machining landing gear beams from 7075 T6 aluminum alloy was analyzed, resulting in significant increases in production efficiency and improvements in the geometric quality of machined parts. During experimental research and implementation testing, special chucks were used on the Schunk Vero-S Aviation system for machining the chassis beam. The results showed an improvement in the quality and accuracy of machined parts compared to traditional clamping methods. Increased production efficiency by minimizing scrap and significantly better surface quality and geometric properties compared to conventional clamping. These studies were conducted as part of a project by Ultratech Sp. z o.o. which was implementing a project co-financed by European Funds "Development and implementation of an innovative clamping method for milling processing of thin-walled structural elements of helicopters and airplanes".